Komitmen pimpinan sebagai moderasi pengaruh good school governance terhadap kinerja sekolah - Iin Indah Novitasari; Rosidi Rosidi; Umi Muawanah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This study aims to analyze the effect of Good School Governance on school performance, analyze the effect of leadership commitment on school performance and the moderating role of leadership commitment on the effect of good school governance on school performance. The research approach uses quantitative methods, the research sample of the principals of Kindergarten institutions in Turen District, Malang Regency as many as 46 respondents. The analytical method used is Moderated Regression Analysis (MRA). The research findings indicate that Good School Governance has a significant influence on school performance, leadership commitment has a significant influence on school performance, the interaction of leadership commitment and Good School Governance has a significant influence on school performance. In terms of managerial implications, the practice of Good School Governance is positively related to school performance and leadership commitment as a moderating variable in an effort to improve school performance and quality. In particular, the commitment of the leadership as a manager, as a leader and the right decision maker to achieve a goal that must be developed and improved.